Evidence for GABA-Induced Systemic GABA Accumulation in Arabidopsis upon Wounding - Scholz, Sandra S.; Malabarba, Jaiana; Reichelt, Michael; Heyer, Monika; Ludewig, Frank; Mithöfer, Axel (Frontiers in Plant Science, 2017)
The non-proteinogenic amino acid γ-aminobutyric acid (GABA) is present in all plant species analyzed so far. Its synthesis is stimulated by either acidic conditions occurring after tissue disruption or higher cytosolic calcium level. In mammals, GABA acts as inhibitory neurotransmitter but its function in plants is still not well understood. Besides its involvement in abiotic stress resistance, GABA has a role in the jasmonate-independent defense against invertebrate pests. While the biochemical basis for GABA accumulation in wounded leaves is obvious, the underlying mechanisms for wounding-induced GABA accumulation in systemic leaves remained unclear. Here, the Arabidopsis thaliana knock-out mutant lines pop2-5, unable to degrade GABA, and tpc1-2, lacking a wounding-induced systemic cytosolic calcium elevation, were employed for a comprehensive investigation of systemic GABA accumulation. A wounding-induced systemic GABA accumulation was detected in tpc1-2 plants demonstrating that an increased calcium level was not involved. Similarly, after both mechanical wounding and Spodoptera littoralis feeding, GABA accumulation in pop2-5 plants was significantly higher in local and systemic leaves, compared to wild-type plants. Consequently, larvae feeding on these GABA-enriched mutant plants grew significantly less. Upon exogenous application of a D2-labeled GABA to wounded leaves of pop2-5 plants, its uptake but no translocation to unwounded leaves was detected. In contrast, an accumulation of endogenous GABA was observed in vascular connected systemic leaves. These results suggest that the systemic accumulation of GABA upon wounding does not depend on the translocation of GABA or on an increase in cytosolic calcium.